2008
DOI: 10.1177/000313480807400219
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Treatment of Hepatic Abscess

Abstract: Many treatment strategies have been proposed for pyogenic liver abscesses; however, the indications for liver resection for treatment have not been studied in a systematic manner. The purpose of our study was to evaluate the role of surgical treatment in pyogenic abscesses and to determine an optimal treatment algorithm. We retrospectively reviewed the medical records of all patients who had a pyogenic liver abscess at Rhode Island Hospital between 1995 and 2002. Abscesses and treatment strategies were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
4
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 18 publications
0
80
4
2
Order By: Relevance
“…For patients who required endoscopic intervention and have raised serum total bilirubin, their obstructed biliary system and with resultant increased likelihood of a septic state and coagulopathy would also mean increased likelihood of conservative management failure. Although it had been proposed that percutaneous drainage be instituted for PLA larger than 5 cm or for unilocated PLA larger than 3 cm , our data showed that the average abscess size and average intravenous antibiotics duration were not predictive for failure of antibiotics‐only therapy. Hence, percutaneous therapy, together with antibiotics, should be instituted early for elderly patients (≥55‐years‐old) with presence of multiple abscesses, malignancy as the etiology or who required endoscopic intervention.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…For patients who required endoscopic intervention and have raised serum total bilirubin, their obstructed biliary system and with resultant increased likelihood of a septic state and coagulopathy would also mean increased likelihood of conservative management failure. Although it had been proposed that percutaneous drainage be instituted for PLA larger than 5 cm or for unilocated PLA larger than 3 cm , our data showed that the average abscess size and average intravenous antibiotics duration were not predictive for failure of antibiotics‐only therapy. Hence, percutaneous therapy, together with antibiotics, should be instituted early for elderly patients (≥55‐years‐old) with presence of multiple abscesses, malignancy as the etiology or who required endoscopic intervention.…”
Section: Discussioncontrasting
confidence: 67%
“…While percutaneous drainage has been shown to be superior to percutaneous aspiration , there is no consensus on an algorithm regarding the surgical management of PLA. Various recommendations include surgical intervention for multi‐loculated PLA larger than 3 cm , patients with APACHE II score ≥15 , or for patients who were not responding clinically to percutaneous therapy . Our study demonstrated that patients with ECOG performance status ≥2, co‐morbidity of hypertension and raised serum total bilirubin were more likely to fail percutaneous therapy and thus require surgical intervention.…”
Section: Discussionmentioning
confidence: 75%
“…Despite this, systemic antibiotic therapy has previously been shown to be an effective treatment for small PLA. Hope et al . retrospectively reviewed 107 PLA cases and found that when the PLA was <3 cm in size, antibiotic treatment alone had a 100% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous treatment methods have generally overtaken open surgery as the treatment of choice; however, studies have showed varied results. Hope et al . retrospectively reviewed patients with PLA, dividing them into three groups depending on abscess size and number of loculi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation